Tendances des relations numériques dans les séquences offensives terminées en but du vainqueur de la Coupe du monde FIFA?2014 - Santos, R.; Duarte, R.; Leão de Andrade, R.; Garganta, J.; Teoldo, I. (Movement & Sport Sciences - Science & Motricité, 2021)
Goal scoring has been regarded as the ultimate indicator of offensive success in soccer. Research on patterns that characterize goal-scoring possessions have frequently employed reductionist approaches. This paper aimed to examine the patterns of numerical relations of open-play goal-scoring possessions of the 2014 FIFA™ World Cup winner team. We hypothesized that a more unstable distribution of players in goal-scoring possessions Germany would be generated in sub-areas of the effective play-space closer to opponents` goal. We analysed 11 video sequences from 6 matches of the German team in this tournament. The uncertainty of teams` numerical advantage within sub-areas of play was calculated for each offensive sequence through Shannon`s entropy. We observed higher entropy within Germany`s Central Offensive (opponents` Central Defensive) sub-area in comparison with the other sub-areas of play. There is a tendency of the German team to generate numerical instability within locations closer to the opponents` goal, possibly due to the shifting of positions, drawing of opposing defenders towards peripheral areas and the creation of spaces for teammates to exploit within this risky zone to the opposition.